2016
DOI: 10.3390/coatings6030033
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Engineered Fire Protective Coatings for Fabrics through Sol-Gel and Layer-by-Layer Methods: An Overview

Abstract: Fabric flammability is a surface-confined phenomenon: in fact, the fabric surface represents the most critical region, through which the mass and heat transfers, responsible for fueling the flame, are controlled and exchanged with the surroundings. More specifically, the heat the fabric surface is exposed to is transferred to the bulk, from which volatile products of thermal degradation diffuse toward the surface and the gas phase, hence feeding the flame. As a consequence, the chemical and physical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 121 publications
1
30
0
Order By: Relevance
“…Conversely, the presence of the silica domains well distributed in the polymer matrix promotes a remarkable decrease of HRR and THR as well: C CPMAS NMR spectra of hybrid polymer before (a, blue) and after (b, red) the thermal treatment acquired at a spin rate 10,000 Hz (color figure online) Fig. 7 Room temperature storage modulus of untreated and thermal treated samples Si NMR spectra of hybrid polymer before (a, blue) and after (b, red) the thermal treatment acquired at a spin rate 10,000 Hz (color figure online) this finding can be explained in terms of formation of a ceramic silica layer, which acts as a thermal shield, hence protecting the underlying materials, slowing down both the diffusion of the volatile flammable degradation products towards the gas phase and the oxygen diffusion towards the degrading material [38].…”
Section: Fire Behaviormentioning
confidence: 99%
“…Conversely, the presence of the silica domains well distributed in the polymer matrix promotes a remarkable decrease of HRR and THR as well: C CPMAS NMR spectra of hybrid polymer before (a, blue) and after (b, red) the thermal treatment acquired at a spin rate 10,000 Hz (color figure online) Fig. 7 Room temperature storage modulus of untreated and thermal treated samples Si NMR spectra of hybrid polymer before (a, blue) and after (b, red) the thermal treatment acquired at a spin rate 10,000 Hz (color figure online) this finding can be explained in terms of formation of a ceramic silica layer, which acts as a thermal shield, hence protecting the underlying materials, slowing down both the diffusion of the volatile flammable degradation products towards the gas phase and the oxygen diffusion towards the degrading material [38].…”
Section: Fire Behaviormentioning
confidence: 99%
“…In recent years, the sol-gel and layer-by-layer (LBL) assembly techniques as the novel coating methods have been reported to be used widely for the flame-retardant treatment of fabrics. 19,20 Especially, flame-retardant coatings prepared via LBL assembly on the polymer surface have received more and more attention due to their simplicity, eco-friendliness, and low impact on the intrinsic properties of substrates. [21][22][23] There are studies being conducted on the improvement of flame retardancy of PET fabrics through the LBL assembly technique.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of surface modification techniques based on layer-by-layer (LbL) self-assembly, the introduction of metal nanoparticles into polyelectrolyte multilayer coatings has proven to be feasible and promising [3][4][5]. The LbL self-assembly approach has been widely adopted in many fields for surface functionalization due to its advantages such as low cost, simple process, controllable coating thickness, and absence of limitations on the substrate size and shape [6,7]. Moreover, since Renneckar first found that polycations can be effectively attached to a wood surface by LbL self-assembly [8], it has been applied successfully in wood surface modifications, with many recent reports on the modification of wood with different materials via the LbL self-assembly process [9][10][11].…”
Section: Introductionmentioning
confidence: 99%